Effects of width and relative position of electrode on transport properties of spintronic nanodevice. (8th February 2019) - Sun, Wei-Yu; Cui, Xing-Qian; Fan, Zhi-Qiang; Nie, Liu-Ying; Zhang, Zhen-Hua
Abstract: Using nonequilibrium Green's function combined with density functional theory, we investigate the spin-resolved transport properties of a single porphycene molecular device with the zigzag graphene nanoribbon electrodes from first-principles calculations. The calculated results show that the width and the relative position of the electrode play an important factor in the spin-resolved I – V characteristics of this molecular device. When a single porphycene molecule connects to electrodes straightly, the device exhibits a significant spin-filtering behavior with a nearly 100% spin filtering efficiency. In addition, negative differential resistance behavior can be observed in its β -spin I – V characteristic. The electrode widening can enhance the negative differential resistance behavior of the β -spin I – V characteristics, but weaken the spin filtering efficiency of the device at high bias voltages. When a single porphycene molecule connects to electrodes un-straightly, the β -spin currents increase linearly in the whole bias range and its I – V characteristics no longer show the negative differential resistance behavior. Moreover, the electrode widening can enhance both α -spin currents and β -spin currents evidently leading to the absent of the spin filtering characteristic.